2011
DOI: 10.1590/s0036-46652011000500004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioactive compounds extracted from euphorbious plants on hematological and biochemical parameters of Channa punctatus

Abstract: SUMMARYChanna punctatus was exposed to four different concentrations of Rutin, Taraxerol and Apigenin. Changes in some hematological parameters of Channa punctatus were assessed to determine the influence of these compounds on test fish. Fish were exposed to sublethal concentrations (80% of LC 50 of 24h) of these compounds for one week. Control fish were also administered for one week. Thereafter, blood samples were obtained from the control and experimental fish. Blood was assayed for selected hematological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…Interestingly, WBC and PLT were the most affected parameters (Table 1). Shahi and Singh (2011) notions are also in agreement with the current findings who reported an increase in the WBC count in response to the pesticides exposure. Similarly, an increase in the levels of Mid %, Gran %, MCV and WBC has also been reported by Dunstan et al (1996), which again justify our findings.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, WBC and PLT were the most affected parameters (Table 1). Shahi and Singh (2011) notions are also in agreement with the current findings who reported an increase in the WBC count in response to the pesticides exposure. Similarly, an increase in the levels of Mid %, Gran %, MCV and WBC has also been reported by Dunstan et al (1996), which again justify our findings.…”
Section: Discussionsupporting
confidence: 94%
“…Tavares-Dias et al (2008) used an automatic blood cell counter for the evaluation of red blood cells (RBC) in two neotropical freshwater teleost species, but all other haematological parameters such as white blood cells (WBC), and thrombocyte counts (TC) were assessed using blood smear techniques. Shahi and Singh (2011) reported that they used an auto analyser to measure parameters such as hematocrit value (PCV), hemoglobin content (Hb), WBC, and RBC in the specimens of Channa punctatus; as they supplied little details of their method, it is difficult to assess the comparability of the values reported.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the search for noble molluscicides of higher efficacy and safety, adoption of efficient application mechanisms could play a decisive role in enhancing their effectiveness. In principle, such molluscicides should be applied in dose as low as possible for environmental, natural resource conservation and economic reasons [ 9 , 10 ]. In the usual immersion method, the molluscicide is added to the water habitat [ 11 , 12 ] and is needed in large amount to titrate the entire water body.…”
Section: Introductionmentioning
confidence: 99%